How to counsel parents after prenatal diagnosis of congenital heart disease: a multidisciplinary approach to develop a questionnaire - Kovacevic, Alexander; Simmelbauer, Andreas; Starystach, Sebastian; Elsässer, Michael; Sohn, Christof; Müller, Andreas; Bär, Stefan; Gorenflo, Matthias (Cardiology in the young, 2018)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS1047951118000318/resource/name/firstPage-S1047951118000318a.jpg